Blood and belief : the circulation of a symbol between Jews and Christians - Biale, David, 1949- (University of California Press, 2007)
David Biale traces the continuing, changing and often clashing roles of blood as both both symbol and substance through the entire sweep of Jewish and Christian history, from Biblical times to the present.
Keywords: Blood -- Religious aspects -- Judaism.; Blood -- Religious aspects -- Christianity.; Blood in the Bible.; Blood accusation -- History.; Antisemitism -- History.; Christianity and antisemitism.; Judaism -- Relations -- Christianity.; Christianity and other religions -- Judaism.; Sang -- Aspect religieux -- Judaïsme.; Sang -- Aspect religieux -- Christianisme.; Sang dans la Bible.; Meurtre rituel -- Histoire.; Antisémitisme -- Histoire.; Christianisme et antisémitisme.; Judaïsme -- Relations -- Christianisme.; Christianisme -- Relations -- Judaïsme.; RELIGION -- Judaism -- Theology.; RELIGION -- Christianity -- General.; Antisemitism; Blood accusation; Blood in the Bible; Blood -- Religious aspects -- Christianity; Blood -- Religious aspects -- Judaism; Christianity; Christianity and antisemitism; Interfaith relations; Judaism; History